The National Climate Budget and the first Nationally Determined Contribution to the Paris Agreement: To what degree are they aligned? - Toby C. Monsod (University of the Philippines, School of Economics (UPSE), 2022)
This paper explores whether and how well the Philippines' Nationally Determined Contribution (NDC) and National Climate Budget (NCB), derived from the national climate change expenditure tagging system (CCET), are aligned. The CCET was operationalized in 2015 to "provide line and oversight agencies with the means to plan, prioritize and monitor the national climate change response allocation and performance", with reference to the outputs and outcomes outlined in the National Climate Change Action Plan 2011-2028 (NCCAP). It finds that the share of climate change expenditures in the primary budget has not been higher than 9 percent and 12 percent, with and without personnel services respectively, undermining the claim that a whole-of-government approach to climate change has been adopted. It also finds that the links between the National Climate Budget and the NDC are tenuous: while the handful of unconditional programs and measures under the latter are supported by the former, the former is populated by climate change adaptation expenditures which are not yet accounted for in the latter but which are likely to have significant mitigation co-benefits. More fundamentally, there are a number of budget items in at least two key departments that are not tagged as CCEs, confirming that departments have a long way to go before the reality and requirements of climate change are properly embedded in planning and budgeting frameworks. One place to start to better integrate the NCCAP is to reformulate agency-level Sector Outcomes, Organizational Outcomes and Performance Indicators (found in Volume II of the GAA) so that these are explicitly climate-aligned.
Keywords: Q54; Q58; Q01; O20; O53; 330; climate change; climate change expenditure tagging system; Nationally Determined Contribution; National Climate Budget; climate-aligned sustainable development